Chronic Disease Management in Children Based on the Five Domains of Health. (9th April 2013) - So, Wing Lung Alvin
Abstract : Through a case study of a child with cystic fibrosis, the interactions among various domains of health have been discussed—namely, biomedical, physical, psychological/behavioural, and social. In pediatrics, development is another key domain relevant to the management of a chronic disease. An individualised management plan for this case has been outlined, and consideration of this framework may be worthwhile when managing other paediatric patients with chronic disease. Patient empowerment and parental education, as well as good co-ordination of health service delivery, are imperative to holistic patient care.